2018
DOI: 10.1002/jemt.23096
|View full text |Cite
|
Sign up to set email alerts
|

Morpho‐palynological assessment of medicinal flora of district Lahore, Pakistan based on LM and SEM

Abstract: This study was carried out to identify 20 high valued medicinal plants of District Lahore, Punjab, Pakistan with the help of the palynological studies. The distinguishing characteristics for selected species were found by systematized methods using light microscopy and Scanning Electron Microscopy. In this study, important pollen qualitative and quantitative features of these medicinal species such as polar and equatorial outline and their diameter, P/E ratio, presence or absence of pore, sculpturing of pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…Palynological characters are also useful in solving complicated problems of inter‐relationship between various taxa and assessment of their status in the classification, particularly regarding the families, sub‐families, tribes, genera, species, and subspecies (Shaheen et al, 2018). Modern taxonomists are identified and differentiate closely related taxa based on palynology.…”
Section: Introductionmentioning
confidence: 99%
“…Palynological characters are also useful in solving complicated problems of inter‐relationship between various taxa and assessment of their status in the classification, particularly regarding the families, sub‐families, tribes, genera, species, and subspecies (Shaheen et al, 2018). Modern taxonomists are identified and differentiate closely related taxa based on palynology.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, morphological tools were used for species identification but with the advancement of science, modern taxonomy also incorporates multiple approaches including palynology (Jalal et al, 2020). Palynomorph characterization is one of the quick and authentic tools for identification and useful in solving complicated problems of interrelationship between various taxa and assessment of their status in the classification particularly with reference to the families, subfamilies, tribes, genera, species, and subspecies (Shaheen et al, 2018).…”
mentioning
confidence: 99%
“…The longest colpi was reported in Plumbago indica (51 μm) whereas the smallest in Aegle marmelos (15.21 μm). The breadth of colpi also showed variations that could be taxonomically valuable (Shaheen et al, 2018). The minimum colpi width was detected in Ocimum sanctum (1.5 μm), however, Plumbago indica reported the uppermost value that is, 49.23 μm (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum and minimum values were observed in Plumbago indica and Aegle marmelos , respectively. The study of Shaheen et al (2018) highlights the significance of pollen fertility in plant taxonomy (Figure 7). Moreover, Shaheen et al (2018) reported a 35% fertility level in Terminalia chebula which is very adjacent to the findings of the current study, that is, 41%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation